Bistatic specular scattering measurements for the estimation of rice crop growth variables using fuzzy inference system at X-, C-, and L-bands - Vishwakarma, A.K.; Prasad, R. (Taylor and Francis Ltd., 2020)
Bistatic scatterometer measurements were performed on the rice crop-bed in the angular range of 20° to 60° for specular direction (Formula presented.) at X-, C- and L-bands for HH-, VV-, and HV-polarizations. The dominant scattering contribution to bistatic specular scattering coefficients ((Formula presented.)) was analysed with the crop growth stages at various angle of incidence. The regression analysis showed high correlation between (Formula presented.) and crop growth variables at 40° angle of incidence for HH-polarization at X-band and for VV-polarization at C- and L-bands. The estimation of rice crop growth variables using subtractive clustering based fuzzy inference system (S-FIS) was done at 40° angle of incidence. The lower values of computed root mean square error (RMSE) between the observed and estimated values showed high potential of developed S-FIS model for the estimation of leaf area index for HH-polarisation at X-band, vegetation water content and fresh biomass for VV-polarization at C- and L-bands, respectively. © 2019 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Bistatic; scatterometer system; fuzzy inference system; rice crop; biomass; leaf area index